3D interactive rhythmic tetris entertainment platform - Low, Chia Zhuang (2019)

(untitled)
The project is an interactive 3D Tetris game, for promoting and encouraging the benefits of interactivity, plus the fast-paced rhythmic elements in the future of gaming industries and also in other areas. The project requires the integration of Orion’s Leap Motion device together with Unity, which requires intense study in game development using C#. This allows manipulating objects in the virtual world through real life objects with the combination of rhythms. The main motivation for this project comes from the uninteresting gameplay of ‘Fragmental 3D’, a 3D Tetris game, which can definitely be improved in various ways by making it challenging, fun and engaging. The project’s main objectives would be improving the gameplay, introducing simpler player control systems, furnishing the project with the impact of rhythms, astounding graphics, enhancing fluidity of the game mechanics, the graphical-user-interface, and also not forgetting about the typical Tetris gameplay. Development of the project can contribute to new ideas coming from UTAR students, whom may have interest to further refine the project with brand new concepts. These concepts can also be applied in real-life applications to innovate new forms of functionality, entertainment and etc. The project will implement rapid application development methodology approach, which occurs by determining the initial version of the application and then develop the next increment of the project in an iterative manner. Regarding the project, player control system has been successfully simplified into a few button presses and finger gestures to trigger events. The GUI is consistent and fluid. Players now have more freedom due to internationalization and tutorials to manage the learning curve. Overall, the development has been going great and close to completion.